2018
DOI: 10.1002/adma.201705195
|View full text |Cite
|
Sign up to set email alerts
|

Shape Memory Polymers for Body Motion Energy Harvesting and Self‐Powered Mechanosensing

Abstract: Growing demand in portable electronics raises a requirement to electronic devices being stretchable, deformable, and durable, for which functional polymers are ideal choices of materials. Here, the first transformable smart energy harvester and self-powered mechanosensation sensor using shape memory polymers is demonstrated. The device is based on the mechanism of a flexible triboelectric nanogenerator using the thermally triggered shape transformation of organic materials for effectively harvesting mechanical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
174
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 276 publications
(174 citation statements)
references
References 40 publications
0
174
0
Order By: Relevance
“…Additionally, the ability to precise control crystalline phases in polymeric materials is likely to prove beneficial in developing next-generation NGs in the coming years. Recently there have been reports on NGs made from shape memory polymers, which provide recovery from large deformation [100] or even self-healing characteristics to cutting damage on NGs [101]. Although there are a few selfhealing NGs reported based on nanostructured materials [102], most of the attempts remain focused on certain bulk polymers, and there may scope to extend such concepts to polymer-based nanocomposites in order to further increase the energy harvesting performance.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Additionally, the ability to precise control crystalline phases in polymeric materials is likely to prove beneficial in developing next-generation NGs in the coming years. Recently there have been reports on NGs made from shape memory polymers, which provide recovery from large deformation [100] or even self-healing characteristics to cutting damage on NGs [101]. Although there are a few selfhealing NGs reported based on nanostructured materials [102], most of the attempts remain focused on certain bulk polymers, and there may scope to extend such concepts to polymer-based nanocomposites in order to further increase the energy harvesting performance.…”
Section: Discussionmentioning
confidence: 99%
“…Fieldemission SEM (FE-SEM) was used to observe freed ZnO NWs ( figure 17(b)) by dissolving the PC template with chlorobenzene followed by heat treatment to burn away the PC template in a furnace at 500 °C for 30 min. XRD analysis of ZnO NWs within the PC template ( figure 17(c)) showed that the preferred orientation of the NWs is [100]. The presence of other peaks in figure 17(c) could be explained by the polycrystalline nature of the electrodeposited ZnO NWs, albeit with an overall preferred orientation.…”
Section: Zno-polymer Nanocomposite Piezoelectric Ngmentioning
confidence: 97%
See 3 more Smart Citations